A taxonomic field investigation in to induced bias in residential real estate appraisals - Diaz III, Julian; Hansz, J. Andrew (International Journal of Strategic Property Management, 2010)
A taxonomic approach to field research was developed and utilized to support empirical and experimental research findings into the impact that incentives/pressures to overvalue have on systematic valuation bias. An expected no‐bias population was defined and valuation judgments from actual, real‐world appraisals were statistically tested against it. The judgments of appraisers presented with no incentive/pressure to over‐value were consistent with the no‐bias population, while the judgments of appraisers presented with incentive/pressure to over‐value were significantly incompatible with the defined no bias population. First Published Online: 18 Oct 2010